PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAAKAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA PEMBELAJARAN PPKn DALAM MATERI MAKNA PERSATUAN DAN KESATUAN DALAM KEBERAGAMAN SISWA KELAS TINGGI SDN PAHLAWAN - Asep Deni Normansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2018)
ABSTRACT The research used is Classroom Action Research which used consist of 2 cycles and through 4 stages. The purpose of this learning outcome is to know the improvement of student learning outcomes by using the model of Picture and Picture learning on learning PPKn in the material meaning of unity and unity in the diversity of high school students (IV) SDN Pahlawan Sub District Banjaran Bandung. After using the model of Picture and Picture learning in the learning of PPKn, the students' learning motivation is more improved, more active and more focused in learning. This research uses Picture and Picture method. The results of this study indicate that with learning Picture and Picture on PPKn subjects can improve student learning outcomes. Looking at the results of the pre-cycle evaluation with the average grade value of 67. In cycle 1 grade average grade 71.67, cycle 2 grade average value of 83.67 has a significant increase. Based on the results of the research, there is an increase in student learning outcomes by using Picture and Picture learning model on learning PPKn in the material meaning of unity and unity in the diversity of high school students (IV) SDN Pahlawan Banjaran District, Bandung Regency can improve student learning outcomes. Keywords: Picture and picture learning model, learning result, Meaning of Unity and Unity in Diversity. ABSTRAK Penelitian yang digunakan adalah Penelitian Tindakan Kelas yang dipakai terdiri dari 2 siklus dan melalui 4 tahapan. Tujuan hasil pembelajaran ini adalah untuk mengetahui peningkatan hasil belajar siswa dengan menggunakan model pembelajaran Picture and Picture pada pembelajaran PPKn dalam materi makna persatuan dan kesatuan dalam keberagaman siswa kelas tinggi (IV) SDN Pahlawan Kecamatan Banjaran Kabupaten Bandung. Setelah menggunakan model pembelajaran Picture and Picture dalam pembelajaran PPKn maka motivasi belajar siswa lebih meningkat, lebih aktif dan lebih fokus dalam pembelajaran. Penelitian ini menggunakan metode Picture and Picture. Hasil penelitian ini menunjukkan bahwa dengan pembelajaran Picture and Picture pada mata pelajaran PPKn dapat meningkatkan hasil belajar siswa. Melihat hasil evaluasi pra siklus dengan nilai rata-rata kelas sebesar 67. Pada siklus 1 nilai rata-rata kelas 71,67, siklus 2 nilai rata-rata kelas sebesar 83,67 mengalami peningkatan yang signifikan. Berdasarkan hasil penelitian yang diperoleh maka terdapat peningkatan hasil belajar siswa dengan menggunakan model pembelajaran Picture and Picture pada pembelajaran PPKn dalam materi makna persatuan dan kesatuan dalam keberagaman siswa kelas tinggi (IV) SDN Pahlawan Kecamatan Banjaran Kabupaten Bandung dapat meningkatkan hasil belajar siswa. Kata Kunci : Model pembelajaran Picture and picture, hasil belajar, Makna Persatuan dan Kesatuan dalam Keberagaman.